LOS CÍRCULOS DE CALIDAD Y SUS EFECTOS EN LA ETAPA DE PLANEAMIENTO DURANTE LA GESTIÓN DE LAS UNIVERSIDADES PRIVADAS EN LIMA METROPOLITANA - Torres Vásquez, Charles Pastor (2012)
Quality becomes of nowadays synonymous the customer’s satisfaction. The problem is that Universities in Lima need to apply a planning of quality circles in order to optimize its management. It was used as method a quantitative – qualitative paradigm, using books, magazines and the Internet sources of information. To resolve the problem, quality circles and modern conceptions of administration empowerment were used to have a correlation in order to know the planning of universities management. As a result, it is been confirmed that quality circles creates a quality and productivity competences in members of an institution, through an equipment. This way of work optimizes planning based on future needs: strategies and politics in behalf of the University in Lima.